Policy-induced environmental technology and inventive efforts: Is there a crowding out? - Hanna Hottenrott; Sascha Rexhäuser (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
Significant policy effort is devoted to stimulate the development, adoption and diffusion of environmentally- friendly technology. Sceptics worry about the effects of regulation-induced environmental technology on firms' competitiveness. Since innovation is a crucial productivity driver, a potential crowding out of inventive efforts could increase the cost of mitigating environmental damage. Using matching techniques, we study the short-term effects of regulation-induced environmental technology on non-green innovative activities for a sample of firms in Germany. We find indeed some evidence for a crowding out of the firms' in-house R&D. The estimated treatment effect is larger for firms that are likely to face financing constraints. However, we do not find negative effects on the number of ongoing R&D projects, investments in innovation-related fixed assets or on the outcome of innovation projects. Likewise, for firms with subsidy-backed environmental innovations no crowding out is found.
Keywords: O32; O33; Q55; 330; Environmental Policy; Regulation; R&D; Technological Change; Innovation; Crowding Out